A view most glorious - Scott, Regina, 1959- (Scott, Regina, 1959- American wonders collection, 2021)
"In 1893 Washington, a headstrong beauty must rely on a rough mountain guide to get her to the top of Mt. Rainier so she can win a wager and save her beloved stepfather's failing bank. But her mountain man has hidden potential-and so, she discovers, does their future together"--